Minimal interventions in the teaching of mathematics - Foster, Colin (2014)
This paper addresses ways in which mathematics pedagogy can benefit from insights gleaned from counselling. Person-centred counselling stresses the value of genuineness, warm empathetic listening and minimal intervention to support people in solving their own problems and developing increased autonomy. Such an approach contrasts starkly with the much more directive and leading interventions often made by mathematics teachers in the classroom. In this position paper I argue that minimal teacher interventions are a powerful way to support students in their learning of mathematics. Drawing on the interplay between a mathematics teacher’s responsibility to teach mathematics and their duty to support students pastorally, I argue that such an approach builds on skills that teachers already possess and has considerable potential to enhance students’ healthy mathematical development.